2006
DOI: 10.1177/0363546506288851
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gamma Irradiation on Anterior Cruciate Ligament Allograft Biomechanical and Biochemical Properties in the Caprine Model at Time Zero and at 6 Months after Surgery

Abstract: Background: High levels of gamma irradiation are required to eliminate the risk of bacterial and viral transmission during implantation of musculoskeletal allografts. The effects of high levels of gamma irradiation on anterior cruciate ligament allograft biomechanics are still not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 37 publications
1
55
0
Order By: Relevance
“…Gamma irradiation reduces mechanical properties of tissues at radiation doses ranging from 25 kGy to 80 kGy on bone-patellar-bone, bone and tendon allografts [1,13,14,17,36,38]. After 50 kGy of radiation, reductions in strength, elastic modulus, and toughness were observed for rabbit tendon allografts [39].…”
Section: Discussionmentioning
confidence: 99%
“…Gamma irradiation reduces mechanical properties of tissues at radiation doses ranging from 25 kGy to 80 kGy on bone-patellar-bone, bone and tendon allografts [1,13,14,17,36,38]. After 50 kGy of radiation, reductions in strength, elastic modulus, and toughness were observed for rabbit tendon allografts [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, reports of disease transmission following ACL reconstruction with nonsterilized allografts, even though very limited in number, underline the importance of graft sterilization [31]. Furthermore, current sterilization techniques have been associated with certain disadvantages, such as interference with biological healing or reduction of mechanical properties of such treated grafts [5,6,13,18,19,24,27]. Peracetic acid has been successfully used to sterilized bone allografts [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Many published studies (Fideler et al, 1995;Curran et al, 2004;Schwartz et al, 2006;Grieb et al, 2006;Balsly et al, 2008) have shown that gamma irradiation significantly alters the initial biomechanical properties of allografts in a dose-dependent manner. A dose as low as 2.5 mrad commonly used by tissue banks has been shown to reduce the initial stiffness and strength of tendon allografts.…”
Section: Introductionmentioning
confidence: 99%